FACTORS AND PEDAGOGICAL OPPORTUNITIES FOR CREATING A SAFE INFORMATION ENVIRONMENT - Bekjan Askarovich Akhmedov (Web of Journals Publishing, 2025)
This article deals with the key factors and pedagogical opportunities involved in fostering a safe information environment among youth. Through analytical research methods, the paper identifies the challenges young people face in the digital space, including misinformation, cyberbullying, and digital addiction. It also examines the role of educational institutions, teachers, and digital literacy programs in promoting safe and responsible online behavior. The findings offer practical recommendations for integrating information safety into educational practices and curricula to build a more secure digital environment for young users.
Keywords: Youth, safe information environment, digital literacy, cyber safety, pedagogy, misinformation, media education, analytical research.